Nuclear Propulsion in Merchant Ship Operations and Implications (Global Journal of Science Frontier Research, 2018)
Introduction-Nuclear fuel cycle and its application to the marine propulsion draw attention to the international and maritime policymakers. It has further been geared up after the Copenhagen summit on global climate change. This worldwide congregation has facilitated to conceptualise the fundamental issues of regarding global warming that leads to global climate change. It seems that the nuclear fuel and its application in marine propulsion and environmental issues should be looked at in parallel. From that point of view, it has been given an assignment on nuclear fuel which is much talked, global concerns, and expectation nowadays. The regular atomic enrichment program and some allegations of handing the nuclear technology over led the global concerns and dismay. With the emergence of atomic technology and clandestine nuclear supply besides global needs for electricity to promote the civilization ahead, all these elements have put the nuclear fuel cycle under controversy and suspicions and mistrust internationally. In this occasion, the efforts have been made to understand the nuclear fuel cycles in broader perspectives and its implications on merchant ship if nuclear propulsion is introduced in broader scale into the marine industry.